A time-stratified case-crossover study on association between short-term exposure to air pollutants and myocardial infarction mortality in Shenzhen - Ziyang ZOU; Ruijun XU; Ziquan LYU; Zhen ZHANG; Jiaxin CHEN; Meilin LI; Xiaoqian GUO; Suli HUANG (环境与职业医学)
BackgroundAir pollution remains a critical public health issue, with persistent exposure to air pollutants continuing to pose significant health risks. Currently, research investigating the association between air pollution and myocardial infarction mortality in Shenzhen remains inadequate. ObjectiveTo quantitatively assess the association between air pollutants and myocardial infarction mortality in residents. MethodsBased on the mortality surveillance system of Shenzhen Center for Disease Control and Prevention, we conducted a time-stratified case-crossover study of 10089 permanent residents who died from myocardial infarction in Shenzhen between 2013 and 2022. Using residential address information, we obtained individual-level exposure data for air pollutants from the China High Air Pollutants dataset and meteorological factors from the China Meteorological Administration Land Data Assimilation System. A time-stratified case-crossover study design was employed to construct a conditional logistic regression model to assess the association between short-term exposure to air pollutants and myocardial infarction mortality. The exposure-response relationship was visualized, and a comprehensive health risk assessment was performed. ResultsThis study included a total of 10 089 cases of myocardial infarction deaths in Shenzhen. The median [interquartile range (IQR)] concentrations of fine particulate matter (PM2.5), inhalable particulate matter (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), and ozone (O3) in Shenzhen from 2013 to 2022 were 24.59 (20.19) μg·m−3, 42.85 (28.42) μg·m−3, 8.53 (3.39) μg·m−3, 29.47 (13.56) μg·m−3, 0.77 (0.27) mg·m−3, and 86.53 (51.39) μg·m−3, respectively. The moving average concentrations of PM2.5 and PM10 over the current day and the previous 2 days (lag02) showed the highest risk of myocardial infarction mortality, with an odds ratio (OR) and 95% confidence interval (95%CI) of 1.004 (1.001, 1.007) and 1.004 (1.002, 1.006), respectively. At lag05, SO2 demonstrated the strongest association with the risk of myocardial infarction mortality, with an OR (95%CI) of 1.042 (1.019, 1.065). The exposure-response relationships of PM2.5, PM10, and SO2 with myocardial infarction mortality were approximately linear, whereas NO2 exhibited a nonlinear relationship. At lag05, the highest risk of myocardial infarction mortality associated with NO2 exposure was observed when the NO2 concentration was ≤21.92 μg·m⁻³, with an OR (95% CI) of 1.024 (1.003, 1.046). The health risk assessment indicated that, using the WHO Air Quality Guidelines as the reference, the local PM2.5 and NO2 exposure led to an excess mortality of 398 and 298 cases, respectively. The sensitivity analysis revealed that after adjusting for O3 and restricting the study period to 2013—2019, the effect estimates for PM2.5, PM10, NO2, and SO2 on myocardial infarction mortality slightly increased. ConclusionShort-term exposure to air pollutants, including PM2.5, PM10, NO2, and SO2, could increase the risk of myocardial infarction mortality. This study provides important scientific evidence for environmental health risk assessment and environmental management in Shenzhen.